(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: A survey of ABO and Rhesus (Rh D) antigens and variants of haemoglobin genes (HbGen) in Oyo state was carried out. This longitudinal study involved the determination of ABO and Rh(D) antigens in 3241 and HbGen in 2622 male and female adults (aged 26-65years) respectively using standard methods. 94.5% of the subjects were Rh(D) positive while 5.5% were Rh(D) negative respectively based on the detection (Positive) or absence (Negative) of Rh(D) antigen. 22.8% of the subjects had ABO blood group A, 26.4% were group B, 4.1% were group AB while 46.7% were group O. Further analysis revealed that 695 (21.4%) of the group A were Apositive while 44 (1.4%) were Anegative. 800 of these subjects (24.7%) were Bpositive while 56 (1.7%) were group Bnegative. 133 (4.1%) showed group AB out of which 125 (3.8%) were ABpositive and 8 (0.3%) were ABnegative. 1513 (46.7%) were group O out of which 1444 (44.6%) were Opositive while 69 (2.1%) were Onegative. HbGen determination showed that 1933 of the subjects (73.7%) had HbGen AA; 553 (21.1%) were AS; 119 (4.5%) were AC; 11 (0.4%) were SC while 3 subjects representing 0.1% and 0.2% each had HbGen SS and CC respectively. Although the results were similar to earlier ones; however, the need for sustained counselling towards eradication of SS genes and increased research towards identifying artificial blood substitutes was highlighted in this work. The increasing need for blood transfusion especially with the increase in various politically/communally motivated emergency situations underscores this fact.